2018
DOI: 10.18553/jmcp.2018.17388
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns Among Patients with Psoriatic Arthritis Treated with a Biologic in the United States: Descriptive Analyses from an Administrative Claims Database

Abstract: This real-world study of treatment patterns for PsA, which used a large U.S. claims database, demonstrated that the majority of patients with PsA discontinued their index biologic (TNFi or anti-IL-12/23 inhibitor) before 12 months. Nearly half of patients initiated an adjunctive medication, many of which were pain and conventional anti-inflammatory medications. DISCLOSURES This study was sponsored by Novartis Pharmaceuticals. Optum was commissioned by Novartis to conduct this study, but employment was not cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 42 publications
4
20
2
Order By: Relevance
“…Our results are in agreement with other studies that pain is a common complaint in patients with PsA treated with TNFi therapy. [8][9][10] Patients reporting severe pain also exhibited more severe psoriasis. As pain is a common symptom of psoriasis, 30 it may be that the skincomponent of PsA, for example, itching, is a contributor to the pain these patients experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in agreement with other studies that pain is a common complaint in patients with PsA treated with TNFi therapy. [8][9][10] Patients reporting severe pain also exhibited more severe psoriasis. As pain is a common symptom of psoriasis, 30 it may be that the skincomponent of PsA, for example, itching, is a contributor to the pain these patients experience.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Pain in PsA may be persistent, and remains present even in patients who achieve minimal disease activity and who are on pharmacotherapy. [8][9][10] People What does this study add?…”
Section: Introductionmentioning
confidence: 91%
“…In cases where physicians reported switching from 1 st to 2 nd immunomodulatory therapy was due to primary lack of efficacy, time to switch to an alternative therapy occurred at a mean of 9.4 months. An observational study based on the nationwide DANBIO registry of 1,422 patients with PsA initiating TNFis demonstrated that 39% switched to a 2 nd TNFi over a median of 2.3 years follow-up and a US study conducted over 4 years reported 22.9% of patients switched biologic therapy [25]. However, in this global analysis of 3,582 patients, at the time of data collection 6.8% had received a 2 nd and 2.5% a 3 rd therapy, with 9.4% and 4.9% receiving a 2 nd and 3 rd therapy in the US respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The age distribution of patients' data in the database population reflects that of the general population in Japan, and data from the MDV has been used in several studies [17][18][19][20]. All patients with an observed diagnosis of PsA according to International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM; codes L40.50, L40.51, L40.52, L40.53, L40.54, and L40.59) [21] between 1 April 2009 and 31 July 2017 were screened for study inclusion. Included patients were required to have a second PsA diagnosis at least 30 days after the first PsA diagnosis in order to increase the specificity of the sample.…”
Section: Methodsmentioning
confidence: 99%